ROUTINE PREOPERATIVE CHEST X-RAY AND ITS IMPACT ON DECISION MAKING IN PATIENTS UNDERGOING ELECTIVE SURGICAL PROCEDURES - Ali, Irum Sabir; Khan, Mumtaz; Khan, Muhammad Atif (Journal of Ayub Medical College Abbottabad, 2013)
Background: It is the routine of our hospital that all patients undergoing any kind of surgery in any specialty are subjected to routine pre-op chest x-ray (CXR). However there is increasing evidence that this practice does not have much influence on patient management and thus could be limited to a very small number of patients in whom it is justified. We conducted this study to know the significance of routine pre-op x-rays chest in patients admitted in a surgical unit for elective surgery and to what extent such routine x-ray affected our surgical intervention. Methods: It is a cross sectional study in which 500 consecutive adult patients admitted in surgical '˜C' unit of Lady Reading Hospital Peshawar, for elective surgical procedures were included. The age, gender, co-morbidity, delay in operation if any was recorded and CXR were reported upon by a qualified radiologist. The influence on decision making regarding fitness of patients for general anaesthesia/surgery was also determined. Data were analysed using SPSS-20. Results: Out of total of 500 chest x-rays 109 (21.8%) were reported to have some abnormality in the film. Out of these 109, 58 were male 51 were female patients. The percentages of abnormal CXR according to age were 13.6%, 35.8%, and 50% in the 16-39 years, 40-69 years and ‰¥70 year age groups respectively. Amongst the patients with abnormal CXR, 30 had their surgery delayed. However in only one patient out of the 30 the delay was on the basis of significant finding on the CXR. Conclusion: Good medical history and clinical examination can save many patients from unnecessary CXR. Preoperative CXR may only be done in patients who have a clear indication for this investigation. Keywords: Surgery, impact, Chest X-ray, pre-operative, fitness, anaesthesia